Evaluación de la dosis de la pulpa de café en la erradicación de paraponera clavata “Isula” (hymenoptera: formicidae), Moyobamba - Herrera Guevara, Miler James (2016)
In the following study, the physical and chemical effect of the coffee bean pulp dose in the eradication of Paraponera clavata "Isula" was evaluated. In addition to producing a significant effect in the eradication of the Paraponera clavata "lsula", the coffee bean pulp also functions as a soil fertilizer, regulates the PH, and increases the essential nutrients ofthe ground for an adequate development ofthe plants which also contributes to the protection ofthe environment as well asan increase in the farmers income. As part ofthis research a Completely Random Block Design was used (CRBD) in which three blocks were stablished with an experimental unit by block and with four Random treatments with the following dose proportion: Treatment 01 or witness (O dose of the coffee bean pulp), Treatment 02 (4 kg ofthe coffee bean pulp), Treatment 03 (5kg ofthe coffee bean pulp), Treatment 04 (6kg ofthe coffee bean pulp) The experiment was developed at the Metoyacu port, at the property that belongs to Mr. Jesus Medina Campos which is a coffee farm located in Moyo bamba City, Moyobamba Province, San Martín State. Data collecting was initiated in each treatment on the first day after the coffee bean pulp was applied, and this process continued for thirty days. Direct count of !sulas (Paraponera Clavata) that were present in the bed conductors was used to stablish the number of ants that were eradicated according to the proposed treatment; this information was then processed. During the 1-month-long phase establishment, treatment 04, at a6 kg dose of coffee bean pulp, had the most influence in the eradication of the Paraponera clavata "lsula".